Proceedings of the Web Conference 2021 2021
DOI: 10.1145/3442381.3450033
|View full text |Cite
|
Sign up to set email alerts
|

Security of Alerting Authorities in the WWW: Measuring Namespaces, DNSSEC, and Web PKI

Abstract: During disasters, crisis, and emergencies the public relies on online services provided by official authorities to receive timely alerts, trustworthy information, and access to relief programs. It is therefore crucial for the authorities to reduce risks when accessing their online services. This includes catering to secure identification of service, secure resolution of name to network service, and content security and privacy as a minimum base for trustworthy communication.In this paper, we take a first look … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…DNSSEC is a DNS extension that enables verification of DNS content but at the same time significantly increases the potential for amplification due to larger response sizes [6,61]. Consequently, benign .gov names, which are subject to a DNSSEC mandate [58], started being misused in amplification attacks [59].…”
Section: Background and Related Workmentioning
confidence: 99%
“…DNSSEC is a DNS extension that enables verification of DNS content but at the same time significantly increases the potential for amplification due to larger response sizes [6,61]. Consequently, benign .gov names, which are subject to a DNSSEC mandate [58], started being misused in amplification attacks [59].…”
Section: Background and Related Workmentioning
confidence: 99%
“…DNSSEC is a security authentication mechanism recommended by Internet Engineering Task Force 32 . However, Fotouhi Tehrani et al 10 found that less than 4% of unique alerting authority (AA) domain names is secured by DNSSEC due to the lack of security awareness and the complexity of deployment. Müller et al 16 analyzed the DNSSEC key management.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, client‐side caching requirements continue to rise. Meanwhile, the client‐side cache insulates users from transient DNS server downtime 9 and reduces network traffic load 10 …”
Section: Introductionmentioning
confidence: 99%